Cone-beam computed tomography in orthopaedics. Issue 4 (August 2022) - Bailey, James; Solan, Matthew; Moore, Emily
Abstract: Orthopaedic practice is closely allied to advances in radiology. Cone-beam computed tomography (CBCT) is an established imaging modality, which is finding novel applications within the field. The principal advantages over conventional computed tomography is that CBCT scanners allow faster, accurate, three-dimensional imaging to be obtained at a fraction of the radiation dosage, using smaller imaging machines. These new scanners can bring CT imaging out of radiology departments and into clinic rooms, emergency departments, community services and operating theatres. This versatility has the potential to change how we practice. Scanners can be orientated vertically – thus allowing patients to stand. Weight-bearing scans allow some pathologies to be better demonstrated. This feature is particularly useful in the lower limb and spinal sub-specialities. This article aims to raise awareness of these new imaging tools, explaining the principles of how they work and introducing ways that they might be applied across sub-specialities within orthopaedic and trauma surgery.